Hardware Approach To Mitigate The Effects Of Module Mismatch In A Grid-Connected Photovoltaic System: A Review - Salam, Zainal; Ramli, Mohd zulkifli; Bassi, Hussain; Sindi, Hatem; Rawa, Muhyaddin (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
This study reviews the hardware approach to mitigate the effects of module mismatch in a grid-connected photovoltaic (PV) system. Unlike software solutions, i.e. the maximum power tracking algorithm, hardware techniques are well suited to enhance energy yield because of their inherent ability to extract energy from the mismatched module. Despite the extra cost of the additional circuitry, hardware techniques have recently gained popularity because of their long-term financial benefits. Notwithstanding the growing interest in this topic, review papers that provide updates on the technological developments of the three main hardware solutions, namely micro inverter,DC power optimizer, and energy recovery circuits, are lacking. This is in contrast to software solutions, which have had a considerable number of reputable reviews. Thus, a comprehensive review paper is appropriate at this juncture to provide up-to-date information on the latest topologies, highlight their merits/drawbacks, and evaluate their comparative performance.